The Effect of Cold Dialysis in Motor and Sensory Symptoms of RLS/WED Occurring During Hemodialysis: A Double-Blind Study - Sakkas, Giorgos K.; Tsaknaki, Evaggelia; Rosa, Clara S. [UNESP]; Giannaki, Christoforos D.; Krase, Argyro A.; Lavdas, Eleftherios; Hadjigeorgiou, Georgios M.; Stefanidis, Ioannis; Karatzaferi, Christina (Lippincott Williams & Wilkins, 2018)
Restless legs syndrome/Willis-Ekbom disease (RLS/WED) is a common sensorimotory disorder affecting almost 30% of hemodialysis (HD) patients. RLS/WED induces discomfort during rest hours, and its symptoms have also been observed during HD sessions. Anecdotal reports suggest that cooling the dialysate solution during dialysis could help patients overcome those symptoms and improve restlessness. The aim of this double-blind study was to assess whether a reduction of the dialysate temperature by 1 degrees C could reduce motor and sensory symptoms of RLS/WED occurring during HD. Thirty-two HD patients participated in the study. Patients were divided into two groups: the RLS (N=16) and the non-RLS groups (N=16). Patients were studied on two different scenarios for two consecutive HD sessions, 1 week apart: 1) standard temperature of the dialysate (37 degrees C) and 2) low temperature of the dialysate (36 degrees C cold dialysis scenario). In all sessions, motor (leg movement per hour of HD [LM/h HD]) and sensory symptoms were assessed. The reduction of dialysate temperature by 1 degrees C was effective in reducing motor symptoms as they assessed the LM/h HD by 36% only in patients with RLS, while a significant interaction was found between LM/h HD affected by temperature and RLS status (p=0.039). Sensory symptoms also reduced by 10% after the reduction of the dialysate temperature. The reduction of the dialysate temperature by 1 degrees C reduced motor symptoms by 36-54% and sensory symptoms by 10% in HD patients with RLS/WED. Cold dialysis could be considered a safe nonpharmacological approach for the amelioration of RLS/WED symptoms occurring during HD.
Keywords: neuromuscular; sleep disorders; exercise; periodic limb movements; fatigue